Historical review of issues on takfir in Malaysia - Razali, Musa; Azarudin, Awang (2015)
The takfir trend is one form of deviation of the mind and behavior among Muslims from the sense of moderation of Islam. This study intends to examine the issues that are being debated, which have eventually brought about this trend within the Muslim community in Malaysia. This study uses the content analysis method for obtaining the necessary data. The study found that the takfir issues that were frequently highlighted in society were the issue of appointment and sharing of power with non-Muslims, implementing Islamic law and separating religion from matters regarding political administration.